Legal Construction of Stateless Person Who Resides in Indonesia in Terrorist Financing - Go Lisanawati; Yaries Mahardika Putro (Jurnal Hukum IUS QUIA IUSTUM, 2023)
This research aims to describe and to analyze Article 2 (2) point g of the Indonesian Terrorism Financing Law and to identify its formal requirements. The approaches used in this paper are statutory and conceptual. As a normative study, this paper exhibits that there is the possibility of Stateless Persons residing in Indonesia as perpetrators of Terrorist Funding in accordance with Article 2 (2) point g of Law No. 9 of 2013. However stateless persons can also be refugees. Thus it is crucial to bear in mind that Article 2 (2) point g of Law No. 9 of 2013 does not regulate the financing of terrorism carried out by refugees. Therefore, proper legal construction is needed to develop adequate provisions to fight terrorism financing. Indonesia must be responsible for providing permanent mechanisms to limit the movement of funds for terrorists involving refugees or asylum seekers.Keywords: Legal Construction, Stateless People, Asylum Seekers, Terrorist Financing, Fefugees. AbstrakPenelitian ini bertujuan untuk mendeskripsikan dan menganalisis Pasal 2 (2) huruf g Undang-Undang Pendanaan Terorisme Indonesia dan memberikan persyaratan formalnya. Jenis pendekatan yang digunakan dalam makalah ini adalah perundang-undangan dan konseptual. Sebagai kajian normatif, makalah ini menunjukkan bahwa adanya kemungkinan Orang Tanpa Kewarganegaraan yang bertempat tinggal di Indonesia sebagai pelaku Pendanaan Teroris sesuai dengan Pasal 2 (2) huruf g Undang-undang No.9 tahun 2013. Orang tanpa kewarganegaraan dapat juga merupakan pengungsi. Mengingat Pasal 2 (2) huruf g Undang-undang No.9 tahun 2013 tidak mengatur terkait dengan pendanaan terorisme yang dilakukan oleh pengungsi. Maka diperlukan konstruksi hukum yang tepat untuk menyusun ketentuan yang memadai untuk melawan pendanaan terorisme. Indonesia harus bertanggung jawab untuk menyediakan mekanisme yang tetap untuk membatasi pergerakan dana bagi teroris yang melibatkan pengungsi atau pencari suaka.Kata kunci: Kontruksi Hukum, Orang Tanpa Kewarganegaraan, Pencari Suaka, Pendanaan Teroris, Pengungsi.